Day‐case percutaneous left atrial appendage occlusion—Safety and efficacy. Issue 7 (23rd September 2018) - Williams, Timothy; Alsanjari, Osama; Parker, Jessica; Gannaway, Alex; Thomson, Catherine; Gomes, Arionilson; Hildick‐Smith, David
Abstract: Objectives: We evaluated the safety and efficacy of percutaneous left atrial appendage (LAA) occlusion performed as a day case procedure. Background: LAA occlusion has been shown to be safe and effective for stroke prevention in patients with atrial fibrillation. It has not been shown if the procedure can safely be performed on a day‐case basis. Methods: Retrospective analysis was made of 117 LAA occlusion procedures in a single large teaching hospital in the UK. Procedural success, procedural complications, length of stay, and readmission data were examined. Results: Successful deployment of a device was possible in all but one patient (whose appendage was too large). Major in‐hospital complications occurred in 1.7% of patients (both femoral vascular). Same‐day discharge was made in 66% of patients overall. Since January 2016, only 3 of 59 patients (5%) have remained in hospital overnight following LAAO. Echocardiography 2–4 hr postprocedure was undertaken prior to discharge. One patient was readmitted within 7 days but this readmission would not have been prevented by overnight stay. Conclusions: LAA occlusion can be safely performed as a day case procedure with acceptable complication rates and no increment of complications related to the lack of routine overnight stay.